EVALUATION OF IN VITRO ANTICANCER ACTIVITY OF ETHANOL EXTRACT OF ALBIZIA SAMAN FLOWERS (World Journal of Current Medical and Pharmaceutical Research, 2019)
To evaluate in vitro anticancer activity on the MCF-7 cell line (Human breast cancer cell line) of Albizia saman (Leguminosae: family) flower extract. The monolayer cells were detached with trypsin-ethylene diamine tetra acetic acid (EDTA) to make single cell suspension and viable cells were counted using a hemocytometer. The cell suspension was diluted with medium containing 5% FBS (Fetal Blood Serum) to obtain final density of 1x105cells/ml. 100µl per well of cell suspension were seeded into 96-well plates at plating density of 10,000 cells/well and incubated to allow for cell attachment at 370C, 5% CO2, 95% air and 100% relative humidity. The results obtained from the in vitro studies performed using the human breast cancer cell line (MCF-7) reveals that the ethanolic extract of Albizia saman flower has a moderate anticancer activity with 94.72% growth inhibition at 200µg/ml. The IC50 value was 120.1µg/ml and the regression value was 0.999.